Self-medication among medical students in Anbar and Fallujah Universities – Iraq: Self medication among medical students - Iraq - Al Shawi, Ameel (Journal of the Faculty of Medicine Baghdad, 2019)
BackgroundIntroduction:Self -medication(SM) is worldwide issue, that have serious adverse effects on individuals and communitiesMethod:A descriptive cross-sectional study was carried out among medical students in Anbar   and Fallujah Universities during the period from February to March 2018.  The subjects were asked to fill a questionnaire that consisted from questions for age, gender, educational level, and employment status, in addition, questions for self-medication history.Results:                                                                           The results revealed that 73% of medical students had practice of self- medication. Higher prevalence of self-medication was among students of 5th study year. Antibiotics was most frequent medicine that used by 137 (49.6%) of the participants, followed by analgesic (29%), and supplements by 40 (14.5%).  The most reasons for using self-medication were previous prescription and advising of pharmacists.Conclusion:                 High prevalence of self- medication among medical students in Falluja & Anbar Universities and there was statistical significant association between gender and self- medication practice.